2009
DOI: 10.1111/j.1471-4159.2009.06124.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of ubiquitin linkages on α‐synuclein induced‐toxicity in a Drosophila model of Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a common movement disorder marked by the loss of dopaminergic (DA) neurons in the brain stem and the presence of intraneuronal inclusions designated as Lewy bodies (LB). The cause of neurodegeneration in PD is not clear, but it has been suggested that protein misfolding and aggregation contribute significantly to the development of the disease. Misfolded and aggregated proteins are cleared by ubiquitin proteasomal system (UPS) and autophagy lysosomal pathway (ALP). Recent studies su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…Many genes and signaling pathways have been reported to regulate the lifespan in model organisms. Rpn11 is one of components in the 26S proteasome and is mainly responsible for "waste" protein degradation by 26S proteasome (Verma et al, 2002;Lee et al, 2009). It was reported that knock down of Rpn11 reduced 26S proteasome activity, caused the accumulation of ubiquitinated proteins and shortened lifespan, while over-expression Rpn11 reduced the ubiquitinated protein accumulation and extended the lifespan (Tonoki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many genes and signaling pathways have been reported to regulate the lifespan in model organisms. Rpn11 is one of components in the 26S proteasome and is mainly responsible for "waste" protein degradation by 26S proteasome (Verma et al, 2002;Lee et al, 2009). It was reported that knock down of Rpn11 reduced 26S proteasome activity, caused the accumulation of ubiquitinated proteins and shortened lifespan, while over-expression Rpn11 reduced the ubiquitinated protein accumulation and extended the lifespan (Tonoki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lee and collaborators demonstrated that the over-expression of ubiquitin has no effect per se on overall adult retinal or dopami nergic neuronal structure or viability (Lee et al, 2009), but co-expression of ubiquitin and a-syn suppresses a-syn-induced motor impairment (negative geotactic locomotor response) and cell degeneration in Drosophila eyes and in the DM1 cluster of dopaminergic neurons. Furthermore, the authors demonstrated that expression of the K48R, and not K63R ubiquitin mutants, suppresses the protective effect of ubiquitin 135 (Lee et al, 2009), suggesting that the ubiquitin mediated neuroprotective effect is potentially dependent on the K48 polyubiquitin linkage, a signature targeting proteins for proteasomal degradation (Lim et al, 2005). Together, these data suggest that a-syn ubiquitination could pro tect against a-syn toxicity in Drosophila PD mod els, by targeting a-syn for proteasomal degradation and enhancing the function of the ubiquitin proteasome system.…”
Section: Ubiquitin-positive Inclusions Are a Neuropathologic Hallmarkmentioning
confidence: 99%
“…Lastly, we used a UAS-based, HA-tagged monoubiquitin transgenic fly line to overexpress wild type ubiquitin (41). Expression of ubiquitin through this line leads to an overall increase in levels of conjugated ubiquitin in intact flies (Fig.…”
Section: Dmusp5 Knockdown Leads To Increased Conjugated Ubiquitin Spementioning
confidence: 99%